(untitled) (Journal of Oriental Studies, 2025)
The article examines Mo Yan’s poetics within the transnational trajectories of magical realism, marking the author’s 70th anniversary as a key context. It proposes to interpret Chinese “hallucinatory realism” as a localized form of magical realism grounded in corporeality and sensory experience. Drawing on the theoretical frameworks of Wendy B. Faris, Amaryll B. Chanady, Mikhail Bakhtin, Jacques Lacan, and Paul Ricoeur, the study develops the concept of a poetics of corporeality, where the marvelous is embedded in the material and phenomenological world. Through close analysis of Mo Yan’s major novels – “Sandalwood Death”, “Life and Death Are Wearing Me Out”, “Frog”, “Pow!”, “The Republic of Wine”, and “Red Sorghum” – the article demonstrates that bodily sensoriality functions as a mediator between memory, history, and power. The marvelous is not detached from the real but naturalized within it, manifesting through theatricality, acoustics, gastronomy, and color. This research advances the idea of corporeal realism as a universal narrative model that expands magical realism beyond its Latin American origins. The study highlights Mo Yan’s contribution to world literature and underscores the significance of Chinese narrative experience for contemporary comparative literary studies.